“I just want to stay out there all day”: A Case Study of Two Special Educators and Five Autistic Children Learning Outside at School - Friedman, Samantha; Morrison, Scott A. (Frontiers in Education, 2021)
School is often stressful for autistic students. Similarly, special educators are susceptible to burnout because of the unique demands of their jobs. There is ample evidence that spending time outside, particularly in nature, has many positive effects on mental, emotional, and physical wellbeing. In this case study of two special educators and five autistic students in a social skills group at an elementary school in the southeastern United States, we sought to identify the effects of moving the class outside several times per week. Findings indicated that while there were challenges, the autistic children experienced numerous affordances that supported development towards achieving Individualized Education Plan goals. Moreover, there were also notable positive effects for the special educators. We found that even with little prior experience, learning outside is possible and beneficial to everyone involved.